Aplicación de una película comestible a base de mucílago de nopal y aceite esencial de orégano en la conservación poscosecha de la fresa (Fragaria x ananassa) - Punina Caiza, Nelly Mercedes (2022)
In this research work, cactus mucilage and oregano essential oil were used in order to obtain an edible film to extend the post-harvest shelf life of strawberries. The mucilage was extracted by crushing, heating, filtration, precipitation, dehydration and storage. Once the edible film was prepared, it was applied to the strawberries at room temperature, where physicochemical parameters were evaluated, recording data during study days 1, 4, 7 and 10. The assessment and incidence of the edible film was carried out using a completely randomised block design with a factorial arrangement A*B +1, with 4 treatments and 3 replicates, where factor A corresponds to the percentage of nopal mucilage at two levels (2%, 4%) and factor B corresponds to the essential oil of oregano, at two levels (0.5%, 1%). The control treatment (T0) was significantly affected in all its physicochemical characteristics from day 4. In the other treatments with the edible film, there are optimal ranges in the physical quality parameters. Treatment T2, composed of 2% cactus mucilage and 1% oregano essential oil, showed better results on day 10, weight loss 22.01; pH was 3.97; soluble solids 9.53; titratable acidity 0.76; moisture percentage 88.36 and texture 1.09. In the microbiological results of the best treatment, 60 CFU/g of total mesophilic aerobes, <10 CFU/g of Staphylococcus aureus, <10 CFU/g of total coliforms, 80 CFU/g of moulds and 20 CFU/g of yeasts were obtained, which is within the values established by bibliographical references. Thus, it is considered that the edible films elaborated with cactus mucilage and oregano essential oil have a positive influence on the postharvest preservation of strawberries.